If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3t + 9t = 20 + -10 + 26 Combine like terms: 3t + 9t = 12t 12t = 20 + -10 + 26 Combine like terms: 20 + -10 = 10 12t = 10 + 26 Combine like terms: 10 + 26 = 36 12t = 36 Solving 12t = 36 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Divide each side by '12'. t = 3 Simplifying t = 3
| 3x+14x-5=0 | | 7(a+3)=49 | | 3(a-1)=2(a+1) | | 13-13=2w-w | | -97-10x=9x+7 | | 7=7c-7 | | 3x+7=-45+10x | | x-9x=80 | | 4e-9=3 | | 3-0.8X=7-X | | x-w=y | | 2-0.66X=5-X | | -55+7=8n | | 4x+33=11x-30 | | 77-3x=33x+17 | | t+3+8(5+t)= | | X+6=0.5X-2 | | 11-9x=61-44x | | 3-28=5a | | 2x+35=5x+12 | | -114-8x=9x+22 | | 4(2X-7)=0 | | 9+5(t+1)+4t= | | 3x+7=-59-9x | | 10(2X-3)=8X | | 7(t+9)+5+t= | | 8t+(7+3t)4+2t= | | 4(X-1)=3(1-X) | | 7+9x=63+x | | 8t+7(7+3t)4+2t= | | 4x+30=11x-40 | | 11-7x=176-42x |